Adapting to the new era: Necessary steps for advancing a robust science - Edna Rabenu; Aharon E. Tziner (Amfiteatru Economic Journal, 2018)
The world has changed tremendously in the past decades. Changes in technology as well as globalization and ferocious business competition phenomena have permeated the workplace and the academic world. These changes and phenomena compel the academic world to adjust itself correspondingly in order to meet the challenges of the new world while maintaining its important role of developing, preserving and spreading human knowledge. The purpose of this paper is to provoke thinking and to generate discussion about the ways the academic world should play out its role in light of the threats and opportunities of the new world. Specifically, it points out some of the difficulties that the academic world is experiencing currently, and proposes some new mechanisms to foster robust academic endeavours.
Keywords: M12; O15; O30; O39; 330; robust science; scientific knowledge; modern research; practitioners' prism; FOMO (fearing of missing out)